Eficácia da inclusão de antibióticos em diluente para criopreservação de sêmen ovino e sua influência na viabilidade espermática - Madeira, Elisângela Mirapalheta (2011)
The objectives of this study were to determine the main bacteria present in ram semen and to evaluate the efficiency of distinct antibiotics in controlling such microorganisms and on sperm viability. Ejaculates were collected from five rams and extended in TRIS-egg yolk. In Experiment 1, the following treatments were tested: control, with no antibiotics; GTLS, with 500 μg/ml of gentamicin, 100 μg/ml of tylosin, 300 μg/ml of lincomycin and 600 μg/ml of spectinomycin; PENSTREP, with 500 μg/ml of penicillin and 100 μg/ml of streptomycin; CEFT, with 50 μg/ml of sodium ceftiofur; and ENRO, with 1000 μg/ml of enrofloxacin. For bacteria identification, samples were collected: the preputial ostium; the artificial vagina; the ejaculates; the semen pool from the five rams; after treatments allocation and stabilization at 5°C; and after thawing. In Experiment 2, variation in the antibiotics concentrations used in Experiment 1 were tested: 25% higher (GTLS+25, PENSTREP+25, CEFT+25 and ENRO+25); 50% higher (GTLS+50, PENSTREP+50, CEFT+50 and ENRO+50); 25% lower (GTLS-25, PENSTREP-25, CEFT-25 and ENRO-25); and 50% lower (GTLS-50, PENSTREP-50, CEFT-50 and ENRO-50). Samples of ram semen were used for counting colony forming units (CFU). The isolated microorganisms were Staphylococcus sp., Klebsiella sp., Corynebacterium sp. and Bacillus sp. The ENRO treatment presented the lowest sperm motility for semen cooled at 5°C and after thawing (P < 0.05), although the post-thawing motility did not differ from that observed for the CEFT and GTLS treatments (P > 0.05). No differences were observed among treatments regarding sperm membrane, acrosome and sperm DNA integrity (P > 0.05). The post-thawing proportion of sperm having DNA integrity was greater for the PENSTREP than for the GTLS treatment (P < 0.05), although sperm DNA integrity may have been impaired by the freezing-thawing process. In experiment 2, the GTLS+50, PENSTREP, ENRO+25 and ENRO+50 treatments presented reduced sperm motility (P < 0.05). All treatments reduced the number of CFU in comparison with the control treatment (P < 0.05). The CFU for the GTLS+50, ENRO+25 and ENRO+50 treatments and the concentrations tested for both those treatments did not differ (P < 0.05), although both were more effective than the PENSTREP and CEFT treatments (P < 0.05). However, the ENRO treatment was associated with reduced sperm motility, especially with high antibiotic concentrations. The treatments did not influence sperm morphology and the integrity of sperm membrane, acrosome and DNA.